Optimasi Sistem Tata Air pada Daerah Irigasi Rawa (Food Estate) Dadahup Kabupaten Kapuas Provinsi Kalimantan Tengah - Rawiyana Galih Anfasa; Elma Yulius; Sri Nuryati; Eko Darma; Anita Setyowati Srie Gunarti; Fajar Prihesnanto (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2023)
The Swamp Irrigation Area (DIR) of Dadahup District is a former Peat Land Development (PLG) with an area of around 21,226 Ha. The water management system at DIR Dadahup utilizes changes in sea tides as a source of water to the land and drainage to drain water out of the land. However, in its implementation, DIR Dadahup experienced several problems such as flooding during the rainy season and experiencing drought during the dry season. These conditions indicate the need for land management and water management systems to overcome existing problems. The purpose of this study was to optimize the water management system for irrigation by optimizing the functions and benefits of swamp land in Dadahup, Kapuas Regency, Central Kalimantan Province. Optimization of the water system is carried out by modeling using the HEC-RAS program. Flow modeling with HEC-RAS in irrigation canals can be simulated into two scenarios, namely scenarios using gates and scenarios with doors and pumps for the rainy and dry seasons. Based on the results of the modeling analysis that has been carried out, the surface elevation during the dry season is in the range of +0.06 ms/d + 0.77 m, which is below the average land elevation (+0.8 m MSL). experience drought because the water in the canals cannot irrigate the land. The water level during the rainy season is in the range of +0.82 ms/d +1.53 m, which is above the average land elevation. It can be concluded that irrigation canals cannot accommodate the overflow of water that occurs at the planned discharge so that the land is flooded. The scenario model is suitable for the Dadahup DIR land use, namely with the door and pump scenario, the water level elevation for the dry season and the rainy season can reach the target of +1.0 m, then the water level elevation for the rainy season can also reach the target of +0, 7m.